2007
DOI: 10.1016/j.cub.2007.01.074
|View full text |Cite
|
Sign up to set email alerts
|

LRK-1, a C. elegans PARK8-Related Kinase, Regulates Axonal-Dendritic Polarity of SV Proteins

Abstract: Neurons are polarized cells that contain distinct sets of proteins in their axons and dendrites. Synaptic vesicles (SV) and many SV proteins are exclusively localized in the presynaptic regions but not in dendrites. Despite their fundamental importance, the mechanisms underlying the polarized localization of SV proteins remain unclear. The transparent nematode Caenorhabditis elegans can be used to examine sorting and transport of SV proteins in vivo. Here, we identify a novel protein kinase LRK-1, a C. elegans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
185
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(190 citation statements)
references
References 24 publications
(27 reference statements)
4
185
0
1
Order By: Relevance
“…http://bmbreports.org Efforts to generate LRRK2 transgenic or deletion mutant animals were also attempted in flies and worms, two very useful experimental animals for this purpose. Abnormal localization of SNB-1, an orthologue of mammalian synaptobrevin2/VAMP2, in both presynaptic and dendritic ends has been reported in the deletion mutant of LRK-1, an orthologue of LRRK2 in C. elegans (22). This result suggested that LRRK2 may be involved in regulation of specific vesicle/cargo transport to proper neurites.…”
Section: Normal and Pathological Features Of Lrrk2mentioning
confidence: 94%
See 1 more Smart Citation
“…http://bmbreports.org Efforts to generate LRRK2 transgenic or deletion mutant animals were also attempted in flies and worms, two very useful experimental animals for this purpose. Abnormal localization of SNB-1, an orthologue of mammalian synaptobrevin2/VAMP2, in both presynaptic and dendritic ends has been reported in the deletion mutant of LRK-1, an orthologue of LRRK2 in C. elegans (22). This result suggested that LRRK2 may be involved in regulation of specific vesicle/cargo transport to proper neurites.…”
Section: Normal and Pathological Features Of Lrrk2mentioning
confidence: 94%
“…The kinase domain of LRRK2 was reported to share homology with mixed-lineage kinase (MLK; 18) and receptor interacting protein kinase (RIPK; 20). Although both LRRK1 and LRRK2 are present in mammals such as human, rat and mouse, only one orthologue of LRRK was identified in Drosophila and C. elegans, respectively called dLRRK and LRK-1 (21,22).…”
Section: Lrrk2mentioning
confidence: 99%
“…In C. elegans, LRK-1 plays a pivotal role in polarized sorting of synaptic vesicle proteins to the Golgi [147]. A LRRK2 interactor, ArfGAP1, associates with the Golgi apparatus as a part of the coat protein I complex [148,149].…”
Section: Effects Of Lrrk2 On Cellular Phenotypes and Physiologymentioning
confidence: 99%
“…In the nematode worm Caenorhabditis elegans, knockout of the paralog LRK-1 suggests a role in polarized sorting of synaptic vesicle proteins to axons by excluding them from dendritespecific transport machinery in the Golgi [73]. LRK-1-knockout worms have a chemosensory deficit, which is interesting since marked olfactory dysfunction is a frequent and early abnormality in PD.…”
Section: Worm Modelsmentioning
confidence: 99%